2004
DOI: 10.1007/s00125-004-1388-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic differences between Arabian and Scandinavian women with gestational diabetes mellitus

Abstract: Aims/hypothesis. Gestational diabetes mellitus is a heterogeneous disorder characterised by impaired insulin secretion and action. Our aim was to study whether autoimmunity, variations in genes affecting insulin secretion and action, or both, contribute to the development of gestational diabetes and whether the pathogenesis of the disease differs between women with a Scandinavian or Arabian background. Methods. We studied a total of 500 unrelated women with gestational diabetes (400 Scandinavian and 100 Arabia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…In the present study, Arab women were characterized by insulin resistance, which, in contrast to our previous findings [14], was no longer apparent after adjustment for BMI. The results of these two studies are not completely comparable since a higher 2-hour cut-off was used in the previous study to define GDM, and furthermore, it was based on data obtained during pregnancy, i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, Arab women were characterized by insulin resistance, which, in contrast to our previous findings [14], was no longer apparent after adjustment for BMI. The results of these two studies are not completely comparable since a higher 2-hour cut-off was used in the previous study to define GDM, and furthermore, it was based on data obtained during pregnancy, i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…This may partly be explained by differences in insulin secretion and action [9][10][11][12][13]. We have previously shown that Arab women with GDM are more insulin resistant during pregnancy than Scandinavian women [14]. This finding stimulated our interest in further studies.…”
Section: Introductionmentioning
confidence: 95%
“…After screening the full-text of the papers, we excluded 34 from the study because they were functional studies or presented duplicate data sets or they did not supply sufficient data about HLA polymorphisms. In our analysis, we finally employed a total of 16 studies 11 13 15 16 17 18 19 21 22 23 24 25 26 27 28 29 and their characteristic features are summarized in Table 1 . The flow of our study is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The link between DQ6 and GDM was discernible in two Swedish populations and one Chinese population 15 19 21 . However, studies of other populations have provided conflicting results that both supported and dismissed the DQ6 link with equal frequencies 11 18 22 24 25 27 28 . Using meta-analysis, we have identified that DQ6 is nominally associated with the etiology of GDM (OR = 0.81, 95% CI = 0.69–0.94) and this association remains significant even when we removed any of the publications included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…So far, genetic predisposition to GDM has been reported for variations in genes involved in insulin resistance and insulin secretion. However, no association could be replicated in different studies [2123]. These discrepancies could be due to lack of power, given the small effect size of most common variants, or to ethnic heterogeneity among different populations.…”
Section: Discussionmentioning
confidence: 99%